1997
DOI: 10.1111/j.1600-051x.1997.tb01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin and clavulanic acid concentrations in gingival crevicular fluid

Abstract: The beta-lactams are bactericidal antibiotics, but some of them may be inactivated by bacterial beta-lactamases which destroy the beta-lactam ring. The inactivation of amoxicillin by beta-lactamases of gram negative anaerobic bacteria can be circumvented by the addition of clavulanic acid, a beta-lactamases inhibitor. Thus, most of these bacteria are susceptible to this combination. The aim of this study was to investigate the concentrations of amoxicillin and clavulanic acid in gingival crevicular fluid (GCF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 13 publications
0
42
0
3
Order By: Relevance
“…The proportion of resistant bacteria ranged from 0.1 to 97% of the total cultivable oral microbiota. Previous studies have shown that concentrations of amoxicillin in the oral cavity after administration of a single antibiotic dose range from 0.1 to 0.5 mg liter Ϫ1 in saliva (14,23) and 1 to 14 mg liter Ϫ1 in gingival crevicular fluid (1,24). The concentration of 8 mg of ampicillin liter Ϫ1 was chosen, as it reflects the concentration found in the oral cavity and is comparable to that used in other relevant studies (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of resistant bacteria ranged from 0.1 to 97% of the total cultivable oral microbiota. Previous studies have shown that concentrations of amoxicillin in the oral cavity after administration of a single antibiotic dose range from 0.1 to 0.5 mg liter Ϫ1 in saliva (14,23) and 1 to 14 mg liter Ϫ1 in gingival crevicular fluid (1,24). The concentration of 8 mg of ampicillin liter Ϫ1 was chosen, as it reflects the concentration found in the oral cavity and is comparable to that used in other relevant studies (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…But selection of AMA was done on empirical basis which was correct because Amoxicillin concentration reaches effectively in gingival crevicular fluid and doxycycline promotes healing in periodontal disease by stabilizing collagens. 16,17 Metronidazole covered effectively against anaerobic bacteria because in Saini et al study 100% aerobes and 80% anaerobes were found in normal gingival sample while 96 to 97% isolated aerobes and anaerobes were found in orodental infection which were found more sensitive to penicillin and metronidazole. 18 Selection of these AMA definitely decreases the risk of infective endocarditis infection by following procedures by adopting antibiotic guideline developed by American Heart Association.…”
Section: Discussionmentioning
confidence: 99%
“…Bu yöntem uyarınca kâğıt şerit oluk içinde tabanda direnç hissedilene kadar ilerletilmektedir. 13,[35][36][37] Diğer oluk içi yöntem olan sığ oluk içi yöntemde kağıt şeritler sulkus girişine (yaklaşık 1 mm derinliğe) konumlandırılmak-tadır. 11,29,35 Sağlıklı dişetinde cep derinliğinin az olması nedeniyle sığ oluk içi yönteminin derin oluk içi yöntemden farkı kalmamaktadır.…”
Section: Kâğıt şErit Yöntemiunclassified
“…Antienflamatuvar ilaçların 23,111,112 ve antibiyotiklerin 21,37,86,113, DOS hacmi ve içeriğini etkileyebildikleri gösterilmiştir. Yine oral kontraseptiflerin, DOS'a olası etkileri uzun süre önce tanımlanmıştır.…”
Section: İlaçlarunclassified